Longitudinal evolution of the Pseudomonas-Derived Cephalosporinase (PDC) structure and activity in a cystic fibrosis patient treated with b-Lactams - Colque, Claudia A. (2022)
Fil: Fil: Colque, Claudia A. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Química Biológica; Argentina.